The Amazon continuum dataset: quantitative metagenomic and metatranscriptomic inventories of the Amazon River plume, June 2010 - Satinsky, Brandon M (BioMed Central, 2014)
BACKGROUND: The Amazon River is by far the world’s largest in terms of volume and area, generating a fluvial export that accounts for about a fifth of riverine input into the world’s oceans. Marine microbial communities of the Western Tropical North Atlantic Ocean are strongly affected by the terrestrial materials carried by the Amazon plume, including dissolved (DOC) and particulate organic carbon (POC) and inorganic nutrients, with impacts on primary productivity and carbon sequestration. RESULTS: We inventoried genes and transcripts at six stations in the Amazon River plume during June 2010. At each station, internal standard-spiked metagenomes, non-selective metatranscriptomes, and poly(A)-selective metatranscriptomes were obtained in duplicate for two discrete size fractions (0.2 to 2.0 μm and 2.0 to 156 μm) using 150 × 150 paired-end Illumina sequencing. Following quality control, the dataset contained 360 million reads of approximately 200 bp average size from Bacteria, Archaea, Eukarya, and viruses. Bacterial metagenomes and metatranscriptomes were dominated by Synechococcus, Prochlorococcus, SAR11, SAR116, and SAR86, with high contributions from SAR324 and Verrucomicrobia at some stations. Diatoms, green picophytoplankton, dinoflagellates, haptophytes, and copepods dominated the eukaryotic genes and transcripts. Gene expression ratios differed by station, size fraction, and microbial group, with transcription levels varying over three orders of magnitude across taxa and environments. CONCLUSIONS: This first comprehensive inventory of microbial genes and transcripts, benchmarked with internal standards for full quantitation, is generating novel insights into biogeochemical processes of the Amazon plume and improving prediction of climate change impacts on the marine biosphere.